Effect of Spearmint (Mentha spicata) on Performance and Blood Serum Parameter of Broiler (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The present study was planned to evaluate the response of broiler chicks to diets containing graded levels of spearmint (Mentha spicata).  A total of 200 , five days-old, unsexes (cob) broiler chicks were used. Chicks were weighed individually and assigned randomly to five groups of 40 chicks per treatment and each treatment was subdivided to four replicates of 10 chicks each. Five experimental diets were formulated (A, B, C, D and E) to meet the nutrient requirements of broiler chicks. The experimental parameters examined were growth performance, serum metabolite, electrolyte and enzyme activities and economic appreciable. Diet (A) Negative      Control (NC), a basal diet without antibiotic or spearmint,  diet B as Positive Control (PC) basal diet supplemented with antibiotic (Neomycin 16 mg/Kg), diets C,D and E were basal diet  supplemented with spearmint at levels of 1,1.5,and 2%, respectively. Result obtained showed that addition of spearmint improved significantly (P